Digital Transformation of Educational Administration: Toward Effective and Sustainable Institutional Governance - Faiqotul Aminah; Malikul Habsi; Muhammaf Fadali Amar; Moh. Sholehuddin Anwar; Lukman Sholeh; Muhammad Irsyad Baitussalam (Global Education Journal, 2026)
Digital transformation has become a key strategy for improving educational administration and strengthening institutional governance in response to rapid technological advancement. This study aims to synthesize the existing literature on the conceptualization, implementation, and outcomes of digital transformation in educational institutions. A qualitative literature review approach was employed by analyzing scholarly articles, policy reports, and conceptual studies related to digital transformation, educational administration, and institutional governance. The findings indicate that digital transformation extends beyond technology adoption and represents a comprehensive organizational change involving digital leadership, governance structures, organizational capability, data governance, and evidence-based decision-making. The literature consistently demonstrates that effective digital transformation enhances administrative efficiency, transparency, accountability, service quality, and institutional resilience while supporting sustainable governance. However, successful implementation depends on the alignment of technological innovation with organizational culture, leadership commitment, and governance reform. This review proposes an integrated conceptual framework that explains the interrelationships among these organizational dimensions. The study contributes to educational administration theory by providing a holistic understanding of digital transformation and offers practical implications for policymakers and educational leaders seeking to develop sustainable governance strategies in increasingly digital educational environments.